EVOLUTION OF WOMEN’S ROLE IN SAUDI ARABIA: FROM TRADITION TO MODERN PUBLIC LIFE - Nigina Kushaeva (Modern American Journals, 2025)
The article is dedicated to exploring the evolving role of women in Saudi Arabia amid the country’s comprehensive reforms and Vision 2030 initiatives. It analyzes significant progress in expanding women’s access to education, science, and participation in public and economic life. The study highlights how these changes reflect a broader cultural and institutional transformation aimed at enhancing gender inclusion and empowering Saudi women as active contributors to the Kingdom’s modernization and development.
Keywords: Saudi Arabia, Crown Prince Mohammed bin Salman, «Vision 2030», Saudi education system, women's participation, unemployment rate, Princess Reema bint Bandar bin Sultan.